Efficacy of hydrogen peroxide wipes for decontamination of AZD1222 adenovirus COVID‐19 vaccine strain on pharmaceutical industry materials. (14th September 2022) - Rhodes, V.P.; Ajorio, A.C.F.B.; da Costa, L.V.; Rodrigues, A.P.; Diniz, V.A.; da Silva Lage, R.V.; da Silva, I.B.; Brandão, M.L.L.
Abstract: This study aimed to evaluate the performance of accelerated hydrogen peroxide® wipes (HPW) for decontamination of the chimpanzee adenovirus AZD1222 vaccine strain used in the production of recombinant COVID‐19 vaccine in a pharmaceutical industry. Two matrices were tested on stainless‐steel (SS) and low‐density‐polyethylene (LDP) surfaces: formulated recombinant COVID‐19 vaccine (FCV) and active pharmaceutical ingredient (API). The samples were spiked, dried and the initial inoculum, possible residue effect (RE) and titre reduction after disinfection with HPW were determined. No RE was observed. The disinfection procedure with HPW resulted in complete decontamination the of AZD1222 adenovirus strain in FCV (≥7·46 and ≥7·49 log10 infectious unit [IFU] ml −1 for SS and LDP carriers respectively) and API (≥8·79 and ≥8·78 log10 IFU ml −1 for SS and LDP carriers respectively). In conclusion, virucidal activity of HPW was satisfactory against the AZD1222 adenovirus strain and can be a good option for disinfection processes of SS and LPD surfaces in pharmaceutical industry facilities during recombinant COVID‐19 vaccine production. This procedure is simple and can be also applied on safety unit cabins and sampling bags made of LDP as well. Abstract : Significance and Impact of Study: The disinfection procedure with hydrogen peroxide® wipes (HPW) resulted in complete decontamination of AZD1222 chimpanzee adenovirus strain in formulated recombinant COVID‐19 vaccine (≥7·46 and ≥7·49 log10 infectious unit [IFU] ml −1 for stainless steel [SS] and low‐density‐polyethylene [LDP] carriers respectively) and active pharmaceutical ingredient (≥8·79 and ≥8·78 log10 IFU ml −1 for SS and LDP carriers respectively). HPW can be a good option for disinfection processes in pharmaceutical industry facilities during recombinant COVID‐19 vaccine production. This procedure is simple and can be also applied on safety unit cabins and sampling bags made of LDP as well.